COVID-19 and cardiovascular imaging: a guide for the practising clinician - Meel, Ruchika; Cupido, Blanche; Pecoraro, Alfonso; Doubell, Anton; Lubbe, Wayne; Ntusi, Ntobeko (SA Heart Journal, 2020)
In the ongoing COVID-19 pandemic, patients with cardiac disease have been the worst afflicted with a high mortality. Cardiac imaging forms an integral part of the armamentarium in the management of these patients. This review focuses on providing a general guide to cardiac imaging in the COVID-19 context for the practising clinician in Africa. These recommendations are likely to be modified as further data emerge on the effect of the SARS-CoV-2 virus on the cardiovascular system.